Possible role of transforming growth factor β as a marker cytokine of type 3 T-helpers in atopic dermatitis pathogenesis - N. A. Pronina; V. S. Sviridova; A. A. Denisov; V. V. Klimov; Ye. N. Kologrivova (Бюллетень сибирской медицины, 2004)
The role of transforming growth factor β (TGF-β) in atopic dermatitis pathogenesis is discussed basing on the analysis of existing data of cellular and molecular mechanisms of allergic inflammation. Up-to date data of the main T-helper (T-h) lymphocyte subpopulations including Tx1, Tx2, Tx3 has been presented. Functions of regulatory T-cell populations and produced cytokines have been described. The main attention has been accented on the TGF-β structure and biological activity as a main Tx3 cytokine. The current information of TGF-β influence on different cell populations and its biological activity realization mechanism is thoroughly discussed. Information relating to the mechanism of cytokine regulation during atopic dermatitis has been summarized. A deep analysis of possible participation of TGF-β in disbalance formation on Tx1 and Tx2 levels, in disturbances of histological derma structure and allergic inflammation timing has been made.